Too old to work, too young to retire? - Andrea Ichino; Guido Schwerdt; Rudolf Winter-Ebmer; Josef Zweimüller (Institute for Advanced Studies (IHS), 2013)
We study whether employment prospects of old and young workers differ after a plant closure. Using Austrian administrative data, we show that old and young workers face similar displacement costs in terms of employment in the long-run, but old workers lose considerably more initially and gain later. We interpret these findings using a search model with retirement as an absorbing state, that we calibrate to match the observed patterns. Our finding is that the dynamics of relative employment losses of old versus young workers after a displacement are mainly explained by different opportunities of transition into retirement. In contrast, differences in layoff rates and job offer arrival rates cannot explain these patterns. Our results support the idea that retirement incentives, more than weak labor demand, are responsible for the low employment rates of older workers.
Keywords: J14; J65; 330; Aging; employability; plant closures; matching